The Dialogue between Student-Reader/Author in University Classroom and Teacher Mediation - Sandra Patrícia Ataíde Ferreira; Maria Prescila Tenório Nascimento de Lima; Fabíola Mônica da Silva Gonçalves (Psicologia, 2011)
Reading is a process of interaction between reader / author / text that results in the production of multiple meanings. This study assessed the reading situations experienced in the classroom in a university context, promoted by the teacher. Two UFPE professors of the teacher training courses took part in the study, as well as, their respective groups, some of licensure courses and others of the pedagogy course. We had fourteen observations of text discussion moments in the classroom through audio recordings and notetaking. According to the results: readings in small groups of students occurred in the two classes, the strategy of questions and answers was used in both cases, intertextuality was always present in the words of teachers and learners in the multiple languages were more commonly present in the group of various degrees by the nature of proposed activities. There was a perceived failure to impose the meanings produced by teachers to students, meaning is negotiated in moments of discussion.